Pay for Performance and Human Resource Management in Japanese Banks (Pravaha, 2024)
The purpose of this paper is to explore the significance of performance-based pay in the context of the "rationalization" of human resource management, with a particular focus on Japanese financial institutions. In the wake of the economic downturn following the collapse of the economic bubble, Japanese financial institutions have faced the need to transform their management policies and business models while also shifting their profit structures. To address these challenges, financial institutions have pursued reforms in human resource management, adopting performance-based compensation systems as a means of securing talent and reducing overall personnel costs.The introduction of performance-based compensation systems in such a context goes beyond mere reorganization of wage structures. It also raises critical questions regarding the relationship between these systems and total wages, as well as their connection to the broader development of human resource management, which includes wage and allowance restructuring and reductions. This paper, therefore, investigates how the job-based human resource system reforms in Japanese financial institutions have reshaped workplace dynamics.